Justice Beyond Legalism: Cultural Appropriation of Totem Poles on the Pacific Northwest Coast - Lefroy, Isabelle (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2019)
This paper attempts to illuminate and problematize the marriage of capitalism and colonialism that results in the widespread appropriation of Indigenous expressions of culture, and in particular, totem poles. This project questions our understanding of totem poles as they have been presented in the marketplace and restores some of the intricate legal meanings to these incredible works. Interdisciplinary and international in scope, this analysis draws from Canadian law, American tribal court law, international law, and Indigenous legal orders. First, I examine Canadian intellectual property law and colonial policies of cultural erasure. Next, I explore legalism as a potential route for solutions to this issue. I then conduct case studies of three totem poles. I examine one totem pole as a commodity, one functioning as a piece of art and someone’s livelihood, and one as part of a Tlingit legal tradition. This last totem, as a materially appropriated object, provides an opportunity to explore the treatment of totem poles in proper context and also functions as a suggested solution to Indigenous art appropriation, more broadly. My intervention on this last totem reframes these issues in a non-Western legal cannon in order to address these difficult legal questions. My examination of these three totems serves to destabilize our understanding of totem poles sold in the marketplace, and to broaden our understanding of totems as manifestations of Indigenous laws.